THE COMPARATIVE STUDY OF THE CONCEPT OF HOME / MOTHERLAND IN THE IDIOLECTS OF THE POETS’ OF RUSSIAN POST-REVOLUTION EMIGRATION WAVE (Philological Studies, 2019)
The paper studies the topic of the influence of the cultural context on the poetry as well as the issue of a cross textual nature of a poetic text. It also considers the influence of life events on the linguistic picture of the world created by a poet made up of such elements as foreign language inclusions, cross cultural concepts, allusions, etc. The article provides comparative study of the concept of HOME and MOTHERLAND in the idiolects of the poets’ of Russian post- Revolution emigration wave, i.e. from 1917 up to 1940. Among the poets whose works have been analyzed and whose poetical idiolects have been compared are Marina Tsvetaeva, Georgy Adamovitch, Ivan Bunin, Georgy Ivanov, Yury Ivask, Boris Poplavsky and others.
Keywords: allusions, citationality, concept, cross-textual studies, cultural context, idiolect, intertextuality, lexical statistics